Analysing local failure scenarios to assess the robustness of steel truss-type bridges. (1st July 2022) - Caredda, Giacomo; Porcu, M. Cristina; Buitrago, Manuel; Bertolesi, Elisa; Adam, José M.
Highlights: This paper deals with the robustness assessment of steel truss-type bridges. Computational simulations validated with real-time data were used for various simulated Damaged Scenarios (DSs). Results indicate that the structure is capable of not triggering a disproportionate collapse after each of the considered DSs. The study was used for stablishing practical recommendations for robust design, reinforcement or monitoring new and existing bridges structures. Abstract: Many of the steel bridge collapses occur in truss-type bridges. This is, in fact, the focus of this study involving an assessment of the robustness of this type of structures based on an actual bridge that the authors had extensively monitored and controlled. Robustness was assessed by means of computer simulations of various Damage Scenarios (DSs) to analyse the structural bridge capacity to efficiently activate Alternative Load Paths (ALPs). The computational models have been previously validated with the results of load tests on the bridge and a laboratory test on a full-scale bridge span. The DSs have considered a series of non-simultaneous failures in different elements. The results indicate that the structure is capable of not triggering a disproportionate collapse after each of the DSs with the help of the efficient activation of ALPs that required the contribution of other elements with extra-strength capacity as well as from the superstructure and the joints working under bending moments. The results were used as the basis for practical recommendations for: i) the design of new steel bridges and the retrofit of existing ones and ii) monitoring the structure for the optimal position of sensors to predict local failures that could spread to the rest of the bridge.